From Truth to Narrative: Postmodern Power and Media Control in Pakistan (Journal of Asian Development Studies, 2026)
This research paper examines the transformation of journalistic practice in Pakistan through a postmodern lens, focusing on the relationships among power, censorship, and media reality. While traditional journalism emphasises objectivity and factual representation, postmodern perspectives suggest that the media increasingly construct narratives shaped by institutional authority and ideological influence. Using a qualitative critical case study design, this research applies Critical Discourse Analysis (CDA) to selected news texts, political talk shows, and regulatory discourse. The study identifies patterns of discursive censorship, narrative framing, and symbolic representation that structure media content. Findings indicate that journalistic discourse operates within negotiated boundaries, in which truth claims are contingent on regulatory constraints and institutional priorities. Media narratives frequently exhibit selective representation, simulation, and ideological framing, contributing to fragmented public understandings of political and social reality. The study argues that media control in Pakistan reflects a broader postmodern condition in which distinctions between representation and reality become increasingly blurred. By integrating postmodern theory with empirical discourse analysis, this research contributes to critical media scholarship and offers insights into the dynamics of power, knowledge production, and mediated communication in contemporary Pakistan.